Sistem Dokumentasi Rancang Bangun Pesawat Udara Berbasis Web Menggunakan Framework CodeIgniter dan PostgreSQL dengan Metode Prototype - Abdul Aziz; Hartono Hartono; Abdul Rohman; Danartomo Kusumoaji (Jurnal Informatika Universitas Pamulang, 2020)
The aircraft design is required to carry out the functions of the Design Organization Approval (DOA), in which there are several positions involved, namely Design Engineer (DE), Compliance Verification Engineer (CVE) and Airworthiness Officer (AWO). In the process, DE makes aircraft designs, CVE will correct the designs that have been made, and AWO will make corrections based on document writing standards. The current problem is that the document checking process takes a long time and requires excessive costs for the use of paper and ink. The solution to solve this problem is by building a web-based system. The system was built using the CodeIgniter framework and PostgreSQL as its database. As for the development of the system itself using the Prototype method. Through this system, the DOA function process will be faster and paperless.